The thermal conductivity jump at crystal-liquid phase transition in CHCl3, C6H6, and CCl4: the action of rotational molecular motion - Pursky, I.O.; Konstantinov, V.A.; Bulakh, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The thermal conductivity of liquid CHCl3, C6H6, and CCl4 was measured by steady-state method under saturated vapour pressure in the temperature areas that correspond to pre-crystallization temperatures. Based on the obtained experimental results, we have investigated the isobaric thermal conductivity jump ΔΛp at crystal–liquid phase transition in CHCl3, C6H6, and CCl4. The contributions of the phonon–phonon and phonon–rotational interaction to the total thermal resistance, in solid and liquid state, are specified using modified method of reduced coordinates. A reduction in the thermal conductivity ΔΛp at crystal–liquid phase transition is explained by a combined effect of variations in positional distribution of molecules and in form of rotational molecular motion.